Doses and application methods of Azospirillum brasilense in irrigated upland rice - Garcia, Nayara F. S. [UNESP]; Arf, Orivaldo [UNESP]; Portugal, Jose R. [UNESP]; Peres, Amanda R. [UNESP]; Rodrigues, Mayara; Penteado, Mariele de S. [UNESP] (Univ Federal Campina Grande, 2016)
The study was carried out in Selviria-MS, in the 2011/12 and 2012/13 agricultural years, aiming to evaluate the efficiency of Azospirillum brasilense in nitrogen fixation in upland rice, as a function of doses and application methods of the inoculant containing this diazotrophic bacterium. The experimental design was randomized blocks, arranged in a 4 x 4 factorial scheme, with 4 doses of inoculant (control without inoculation, 100, 200 and 300 mL of the commercial product ha(-1)) and 4 application methods (seed inoculation, application in the sowing furrow, soil spraying after sowing, and foliar spraying at the beginning of plant tillering), with 4 replicates. During the experiment, the agronomic characteristics, production components and yield of the rice crop were evaluated. It was concluded that the inoculant containing Azospirillum brasilense promotes increase (19%) in the yield of upland rice under sprinkler irrigation when used at the dose of 200 mL ha(-1), regardless of the application methods.
Keywords: Oryza sativa L.; diazotrophic; cv. IAC 202; nitrogen fixation; grain yield